Sheep and Cattle Reservoirs in the Highest Human Fascioliasis Hyperendemic Area: Experimental Transmission Capacity, Field Epidemiology, and Control Within a One Health Initiative in Bolivia - Mas-Coma, Santiago; Buchon, Paola; Funatsu, Ilra R.; Angles, Rene; Artigas, Patricio; Valero, M. Adela; Bargues, M. Dolores (Frontiers in Veterinary Science, 2020)
The Northern Bolivian Altiplano is the human fascioliasis hyperendemic area where the highest prevalences and intensities of infection by Fasciola hepatica in humans have been reported. Four animal species are the reservoir species for F. hepatica in this area, namely, sheep, cattle, pigs, and donkeys. Livestock for the Aymara inhabitants is crucial because vegetable cultures are not viable due to the inhospitality of the very high altitude of 3,820–4,100 m. A One Health initiative has been implemented in this area in recent years, as the first such control action in a human endemic area ever. Among the different control axes included, special focus is devoted to the two main reservoirs sheep and cattle. Egg embryonation, miracidial infectivity, intramolluscan development, cercarial production, infected snail survival, and metacercarial infectivity were experimentally studied in altiplanic sheep and cattle isolates. These laboratory studies were performed using altiplanic isolates of the lymnaeid species Galba truncatula, the only vector present in the hyperendemic area. Experiments were made at constant 12 h day/12 h night and varying 20/20°C and 22/5°C photoperiods. Infections were implemented using mono-, bi-, and trimiracidial doses. Results demonstrate that sheep and cattle have the capacity to assure F. hepatica transmission in this very high-altitude area. Field surveys included prevalence studies by coprology on fecal samples from 1,202 sheep and 2,690 cattle collected from different zones of the Northern Bolivian Altiplano. Prevalences were pronouncedly higher and more homogeneous in sheep (63.1%; range: 38.9–68.5%) than in cattle (20.6%; range: 8.2–43.3%) in each one of the different zones. Although similarities between the prevalences in sheep and cattle appeared in the zones of the highest and lowest infection rates, this disappeared in the other zones due to cattle treatments. Comparison with past surveys demonstrates that this hyperendemic area is stable from the disease transmission point of view. Therefore, the control design should prioritize sheep and cattle within the One Health action. Studies performed in the Bolivian Altiplano furnish a baseline for future initiatives to assess the transmission and epidemiological characteristics of fascioliasis in the way for its control in other high altitude Andean endemic areas.